2022
DOI: 10.2147/opth.s359309
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Buckling: A Look at the Past, Present and Future in View of Recent Findings on the Importance of Photoreceptor Re-Alignment Following Retinal Re-Attachment

Abstract: Scleral buckling (SB) remains an important technique to master for those interested in treating rhegmatogenous retinal detachment (RRD). Several ways to repair RRD include pneumatic retinopexy (PR), pars plana vitrectomy (PPV), SB or a combination of these. There is a growing worldwide trend that favors PPV as the preferred method for retinal reattachment of primary uncomplicated RRD. Reimbursement issues, operating room access, and technological advances in PPV that improve retinal visualization and less expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…Chandelier scleral buckling has been reported to have intraoperative risks similar to those of standard scleral buckling with regard to choroidal and subretinal hemorrhages and scleral perforations. 43,46 The most common postoperative complications of chandelier scleral buckling were also similar to those of standard scleral buckling, including redetachment, PVR, and elevated IOP. 46 These complications are more related to the scleral buckle technique itself rather than the implementation of the chandelier viewing device.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Chandelier scleral buckling has been reported to have intraoperative risks similar to those of standard scleral buckling with regard to choroidal and subretinal hemorrhages and scleral perforations. 43,46 The most common postoperative complications of chandelier scleral buckling were also similar to those of standard scleral buckling, including redetachment, PVR, and elevated IOP. 46 These complications are more related to the scleral buckle technique itself rather than the implementation of the chandelier viewing device.…”
Section: Discussionmentioning
confidence: 76%
“…43,46 The most common postoperative complications of chandelier scleral buckling were also similar to those of standard scleral buckling, including redetachment, PVR, and elevated IOP. 46 These complications are more related to the scleral buckle technique itself rather than the implementation of the chandelier viewing device. Unfortunately, our analysis was unable to directly compare complication rates between chandelier scleral buckling and standard scleral buckling because the majority of studies only reported complications for chandelier scleral buckling.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study showed that when performing SB, 3D surgery proved safe and offered non-inferior results to conventional microscope viewing [ 43 ]. Surgical time reduction seems another valuable feature in chandelier-assisted scleral buckling (CSB) compared to conventional SB [ 44 ]. Although chandelier insertion changed SB from an extraocular to an intraocular procedure, there is rarely evidence of complications related to this procedure, such as IOL displacement, iatrogenic break [ 24 ], retinal incarceration, vitreous prolapse, or endophthalmitis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As this has become more readily accessible to surgeons there has been increasing literature to support its non‐inferiority to standard indirect viewing. To date, chandelier assisted scleral buckle repair has shown primary reattachment rates ranging from 78% to 95% which is at least equally favourable to our conventional repair methods 44–46 . Unfortunately, more data are needed to see if the possible complications from disturbing the vitreous (i.e., prolapse and iatrogenic breaks) may make this technique less advantageous than it would appear.…”
Section: Scleral Bucklementioning
confidence: 99%